The Role of E-Commerce in Shaping the Income of Traditional Traders: A Case Study of Segiri Market, Samarinda - Nabila Anriani Aprilia; Eka Kurniati; Risa Puji Haspanti; Febriyanti Nur Hafifah; Areta Nur Fatimah Azalia (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research focuses on the effect of e-commerce on the income of traditional traders at Segiri Market in Samarinda. Using a quantitative approach, the study applies Ordinary Least Squares (OLS) with a simple linear regression model. In this model, e-commerce adoption serves as the independent variable, while traders’ income is the dependent variable. The results show that e-commerce has a positive and significant effect on traders’ income, with a regression coefficient of 0.647 and a p-value of 0.000. This indicates that greater use of e-commerce platforms leads to higher trader income. The constant value of 18.503 suggests that traders can still earn income without e-commerce, but at a lower level than those who actively use digital platforms. The t-test and F-test confirm the model’s statistical significance and reliability, with an F-value of 74.76 and a p-value of 0.000. An R² value of 0.567 means that 56.7% of the variation in income is explained by e-commerce adoption, while the remaining 43.3% is influenced by other factors. These findings support the Technology Acceptance Model (TAM), which emphasizes that perceived usefulness and ease of use encourage traditional traders to adopt digital technologies. Overall, e-commerce acts as a complementary strategy that increases income and strengthens competitiveness in traditional markets.